Efficiency of European Universities: A Comparison of Peers - Lars Herberholz; Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2020)
The European higher education landscape has become increasingly integrated causing competition among universities that is no longer bound to national borders. In view of this development, the present paper investigates the relative efficiency of 450 European universities between 2011 and 2014. The novelty of our approach lies in its extended coverage of university outputs and in the thorough peer-group selection process that accounts for high diversity in subject profiles. More specifically, assignment to peer-groups builds on proximity in subject space to ensure valid comparisons between universities. Exploring potential efficiency drivers, we uncover considerable effect heterogeneity between subject clusters, which is indicative of distinct technologies and calls for carefully designed policy measures. Yet institutional size and the ability to seek external funding are largely identified to be primary efficiency drivers.
Keywords: H52; I23; I28; 330; university efficiency; peer selection; data envelopment analysis; clustering